Creation and Movement of Action Plain For The Work Culture of Religious-Based Educational Organizations - Herman Herman; Rena Juliana; Khairuddin Hasan (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This article describes the creation and movement of action plans for the work culture of religious-based educational organizations. The working culture of religious educational organizations is determined by the elements heart (qalbu), mind (aql) and passion. Heart (qalbu) controls the quality of academic and non-academic services supported by emotional intelligence, spirituality, and noble personality. Mind (aql) controls the quality of graduate results as educational production supported by intellectual, humanitarian, argumentative and rational intelligence. Passion controls the potential for good and bad quality of service results and educational products supported by mind (aql) and heart (qalbu). This study uses a qualitative library research method with a phenomenological approach in analyzing the factual conditions of educational organizations. The data analysis technique is by reviewing various relevant literatures with the focus of the problem being discussed. The results showed that the work culture of religious educational organizations was built up and further developed by creating a work culture by changing the way of thinking of working with the heart (qalbu), the perception of working with mind and heart (qalbu) and shaping work behavior to preventive, corrective and curative way. Then make an action plan movement on work culture by accelerating internalization of the values of work culture, working all day and all the time, effectively communicating, smoothly coordinating between areas and organizational units, and meticulous in monitoring and evaluating.